2022
DOI: 10.24928/2022/0124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Last Planner® System Adoption Level on Project Management and Communication

Abstract: Construction projects require complex management of people, resources and goals. The Last Planner® System (LPS) provides a systematic framework based on short cycles of work preparation, commitment, and control to allow implementing corrective actions. Successful LPS implementations require the combination of homogeneous mature practices and efficient horizontal collaboration. Nevertheless, partial implementations prevent liking collaboration through mid-term planning, the make-ready process and short-term wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…These studies support the statement that horizontal collaboration in planning and work preparation is key to support the LPS virtuous cycle of proactive planning, committing and control, which in terms of MRP, corresponds to (1) efficient constraint identification and (2) reliable removal (Ballard & Tommelein, 2016). Horizontal collaboration facilitates that last planners take part in this process (Lagos et al, 2022), while the strength of these interactions, i.e. close collaboration between multiple parties, leads to work preparation reliability (Castillo, Alarcón, & Pellicer, 2018).…”
Section: Literature Review Body Of Knowledge Regarding the Problem Spacesupporting
confidence: 76%
See 3 more Smart Citations
“…These studies support the statement that horizontal collaboration in planning and work preparation is key to support the LPS virtuous cycle of proactive planning, committing and control, which in terms of MRP, corresponds to (1) efficient constraint identification and (2) reliable removal (Ballard & Tommelein, 2016). Horizontal collaboration facilitates that last planners take part in this process (Lagos et al, 2022), while the strength of these interactions, i.e. close collaboration between multiple parties, leads to work preparation reliability (Castillo, Alarcón, & Pellicer, 2018).…”
Section: Literature Review Body Of Knowledge Regarding the Problem Spacesupporting
confidence: 76%
“…A subsequent study by the same authors also correlated the network strength metrics with benefits in quality, safety, costs, and productivity (Castillo, Alarcón, & Pellicer, 2018). Furthermore, a case study using a similar methodology to compare two projects of similar characteristics and LPS experience, observed that the project with higher horizontal collaboration in planning and problem solving exhibited significantly better MRP practices and long-term schedule compliance, while the project with a more traditional top-down management approach exhibited work-preparation silos that allowed to obtain high PPCs but prevented them from sustaining high long-term schedule performance due to the lack of flexibility of the WB (Lagos et al, 2022).…”
Section: Literature Review Body Of Knowledge Regarding the Problem Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Cisterna et al (2018) examined the suitability of Social Network Analysis (SNA) in the AEC industry and identified the influence of project complexity and cultural aspects. Lastly, Lagos et al (2022) studied the LPS adoption levels, team collaboration, and project performance by comparing two Chilean construction projects, finding that mature LPS adoption significantly aids collaboration and performance. While these studies introduced a much-needed perspective on how collaboration may be assessed and evaluated, empirical and numerical methods that pertain to the direct quantification of either collaboration or the impacts of collaboration on the performance of a project are still unaddressed.…”
Section: Means To Measure Collaboration In Constructionmentioning
confidence: 99%